Effectiveness of urban green space on stress relief at Bukit Jalil - Lee, Yee Shian (2019)
This study examined the effectiveness of urban green space on stress relief at Bukit Jalil. Thirty students (male: 15, female: 15; mean age ± standard error: 22.93 ± 0.191) from the Faculty of Forestry, Universiti Putra Malaysia (UPM) participated in a 2 days experiment at Bukit Jalil Park and Bukit Jalil Street. Participants walked along the given route in both areas at the specific time set for 20 minutes. Blood pressure measurements were recorded before and after walking in both areas. The psychometric tests Profile of Mood States (POMS), Positive and Negative Affect Schedule (PANAS), Perceived Stress Scale (PSS) and Restoration Outcome Scale (ROS) were completed in the pre-test and post-test to identify the significant effect after walking in both study areas. The results indicated that systolic and diastolic pressure decreased in the urban green space and systolic pressure increase in the city. In the ROS test, participants show a significant difference (p<.001), when comparing both study areas. Urban green space shows higher mean scores in all six restorative statements, while the city had lower restorative means scores. In the POMS test, the result of Total Mood Disturbance (TMD) indicated a significant difference (p<.001) when comparing the pre-test and post-test of walking in UGS. TMD indicate a lower value in UGS and higher value in the city. Therefore, TMD indicated that participants have more mood disturbance in the city. In the PANAS test, sums of positive attitude were increased (p<.001) and sums of negative attitude were decreased (p<.001) in the urban green space, whereas, both total positive and negative attitude were reduced in the city. For PSS test, urban green space and city show a significant difference (p<.05) in the post-test. Therefore, there are differences towards urban users’ health impact between UGS and City. Hence, people are encouraged to spend more time and start walking in urban green space for better stress relief.